LEGAL RECOGNITION OF SAME-SEX COUPLES’ FAMILY RELATIONSHIPS IN RESIDENCE PERMIT ISSUANCE - Okropiridze, Tsisia; Bakhtadze, Ketevan (MIGRATION POLICY AND LEGAL RESPONSES, 2025)
This comprehensive legal analysis examines the systemic challenges confronting same-sex couples in securing residence permits for family reunification purposes, with particular emphasis on the discriminatory implications of Georgia's 2024 "Law on Family Values and Protection of Minors." Through rigorous comparative jurisprudential methodology, the research scrutinizes the evolving European legal landscape regarding recognition of same-sex family relationships in transnational contexts. The study employs normative and comparative legal research frameworks to evaluate Georgian legislation against established European Court of Human Rights jurisprudence and Court of Justice of the European Union precedents. Critical analytical dimensions encompass procedural barriers in residence permit issuance, the autonomous concept of "family life" under Article 8 ECHR, and the discriminatory effects of restrictive national legislation on same-sex couples' fundamental rights. Key methodological approaches include comparative institutional analysis of European legal frameworks, doctrinal examination of residence permit procedures, systematic jurisprudential review of ECtHR and CJEU case law, and critical evaluation of administrative discretionary authority. The research demonstrates that Georgia's absolute prohibition on recognizing foreign-registered same-sex marriages and civil partnerships constitutes discrimination based on sexual orientation, fundamentally violating international human rights standards. The analysis reveals a systemic contradiction between progressive European jurisprudence recognizing same-sex couples' right to family life and restrictive national implementation mechanisms, necessitating comprehensive legal reform to harmonize domestic legislation with transnational human rights obligations.